Nursing education reform in South Africa - lessons from a policy analysis study - Duane Blaauw; Prudence Ditlopo; Laetitia C. Rispel (Taylor & Francis Group, 2014)
Background: Nursing education reform is identified as an important strategy for enhancing health workforce performance, and thereby improving the functioning of health systems. Globally, a predominant trend in such reform is towards greater professionalisation and university-based education. Related nursing education reform in South Africa culminated in a new Framework for Nursing Qualifications in 2013. Objective: We undertook a policy analysis study of the development of the new Nursing Qualifications Framework in South Africa. Design: We used a policy analysis framework derived from Walt and Gilson that interrogated the context, content, actors, and processes of policy development and implementation. Following informed consent, in-depth interviews were conducted with 28 key informants from national and provincial government; the South African Nursing Council; the national nursing association; nursing academics, managers, and educators; and other nursing organisations. The interviews were complemented with a review of relevant legislation and policy documents. Documents and interview transcripts were coded thematically using Atlas-ti software. Results: The revision of nursing qualifications was part of the post-apartheid transformation of nursing, but was also influenced by changes in the education sector. The policy process took more than 10 years to complete and the final Regulations were promulgated in 2013. The two most important changes are the requirement for a baccalaureate degree to qualify as a professional nurse and abolishing the enrolled nurse with 2 years training in favour of a staff nurse with a 3-year college diploma. Respondents criticised slow progress, weak governance by the Nursing Council and the Department of Health, limited planning for implementation, and the inappropriateness of the proposals for South Africa. Conclusions: The study found significant weaknesses in the policy capacity of the main institutions responsible for the leadership and governance of nursing in South Africa, which will need to be addressed if important nursing education reforms are to be realised.